Preliminary work about the basis data for monitoring youth soccer team planning training - Ceruso, R.; Esposito, G.; Federici, A.; Valentini, M.; D'Isanto, T. (Journal of Human Sport & Exercise, 2019)
The youth soccer is always important especially for the assessment and the data of development of skills. The monitoring of them it could be important for the trainer to reorganize the planning of training and for the adaptation to individual athlete Aim of the study is to recruit the quantitative data about the anthropometric and performance aspects for reutilize to rearrangement of training planning. Method is experimental and has to carry out the usual parameters for monitoring the trainings. Anthropometric data are weight, height, BMI and performance data are Vo2max (Cooper) speed triangle test (three corner run) and speed test with (dribbling) on a sample are 13 athletes of 13 years old that play championship under 14 . BMI Data shows 6 weight, 4 in overweight risk and 3 in overweight. Cooper test data shows 2 above- average, 5 average, 5 below average and 1 poor. Mean speed triangle test 32.38 seconds, mean dibbling test 25.39 seconds. The results have to be useful for tool method of training.